TEACHER AND STUDENT PERCEPTIONS OF CHATGPT IN ACADEMIC WRITING AND ESL CLASSROOMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the perceptions of teachers and students regarding the use of ChatGPT in academic writing within English as a Second Language (ESL) classrooms. With artificial intelligence (AI) increasingly influencing language learning, tools like ChatGPT are becoming accessible and popular among ESL learners. The research investigates the perceived benefits, drawbacks, ethical concerns, and pedagogical implications of integrating ChatGPT into ESL writing instruction. Through a mixed-methods approach involving surveys and interviews, the study identifies emerging attitudes and practices, highlighting the potential of ChatGPT to enhance ESL writing skills while also raising important concerns about academic integrity and student dependence.